A Planned Cesarean Section-Hysterectomy For Placenta Previa Totalis Percreta In Patient With History Of Two Cesarean Sections - Nainggolan, Julita (Medicinus, 2015)
The presence of placenta previa may be associated with placenta accreta[1].  Maternal and fetal morbidity and mortality from placenta previa accreta are considerable and are associated with high demands on health resources. With the rising incidence of caesarean sections combined with increasing maternal age, the number of cases of placenta praevia and its complications, including placenta accreta, will continue to increase[2]. Here, we present a case of  placenta previa totalis percreta in previous cesarean section twice. In this case, patient with placenta previa totalis-percreta we diagnosed and prepared  proper management with the involvement of multidisciplinary team. We reduced blood loss by performing total abdominal hysterectomy immediately after delivered the baby and the postoperative course was uneventful.Keywords: Cesarean Section-Hysterectomy, placenta accreta, placenta percreta, placenta previa